English Kids’ Songs: Effective Media for Teaching Vocabulary - Rochma, Annisa; Mukminatus Zuhriyah (Discovery, 2025)
This research aims to find out the effectiveness of using English kids' songs to teach vocabulary. It was conducted in a private elementary school located in Jombang area in the academic year of 2023-2024. The population of this research was the fourth-grade students, consisting of three classes with a total of 62 students. The sample, selected using purposive sampling, included 18 students of class IV B. This study used a pre-experimental design with pre-tests and post-tests to measure students' vocabulary improvement before and after learning using English kids' songs. The pre-test checked their initial vocabulary while the post-test measured their progress. The results were analyzed by descriptive statistics and a-paired sample t-test. The results showed that vocabulary before being treatment was still "fairly sufficient" with the mean score of 59,44.  After being taught using English kids’ songs, the students’ vocabulary mean score increased from 59.44 to 88.89. The mean score, which was initially categorized as "fairly sufficient," has now risen to the "excellent" category, reflecting a notable enhancement in the student's vocabulary mastery. The paired sample t- test results showed a significance value of 0.000, which is less than 0.05, meaning the improvement was statistically significant. It means that English kids' songs as the media is effective for teaching vocabulary at an elementary school. This research provides strong evidence that innovative media such as English kids' songs can be a concrete solution to the challenges of vocabulary learning in school especially at an elementary level.